Analisis Pemahaman Konsep Belajar Siswa pada Materi Perbandingan yang Ditinjau dari Gender - Hanifah, Umi; Julaikha, Siti; Mufidah, Nur (Jurnal Likhitaprajna, 2024)
Concept understanding in terms of gender has an important role in learning mathematics which will strengthen students' memories in receiving mathematical material that is imaginary so it is necessary to understand the concept first. The purpose of this study was to determine how the ability to understand the concepts of male and female students on Student Comparison material at SMP NU Lekok. The type of research used is qualitative research. The research subjects were 4 students consisting of 2 male students and 2 female students. Data collection techniques are tests and interviews. The results of this study showed that there were still male students who could not restate the concept of comparison, including the medium category, while for women, they could meet the indicators of restating a concept, including the high category; indicators of classifying objects according to their concepts, male students included the medium category, female students included the high category; indicators of presenting concepts in the form of mathematical representations, male students included the medium category, female students included the high category; indicators of using, utilising and selecting procedures or operations, male and female students included the low category; indicators of applying concepts or algorithms, male and female students included the medium category.